PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM TRANSAKSI MENGGUNAKAN SISTEM PEMBAYARAN BERBASIS QRIS (QUICK RESPONSE CODE INDONESIAN STANDARD) - Febri Nur Anisa; Fitika Andraini (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The current rapid development of technology or commonly referred to as the industrial era 4.0, which affects individuals in interacting. The emergence of the term industry 4.0 has also affected significant changes in economic patterns and income and quality of life, which has an impact on the use of a payment system based on the Quick Response Code Indonesian Standard. Even though it has a positive impact on its use QRIS is a payment method that is still in the process of being developed, does it have certain legal protections given to its consumers? Therefore this study aims to see more clearly what kind of protection is provided by electronic transaction operators to their consumers. This study uses a descriptive normative method with qualitative techniques. The results of this study are that the application of QRIS as a payment method is protected by several regulations issued by Bank Indonesia institutions as well as regulations issued by government regulations and the Consumer Protection Act, which provide security and convenience for consumers in transactions.